Hand Grip Strength, Arm Muscles Power, and Flexibility: Key Contributions to Wrestling Athlete Slam Success - Alifiansyah, Rafi; Destriana, Destriana; Iyakrus, Iyakrus (Journal of Sport Science and Fitness, 2024)
This quantitative research aimed to examine the relationship between hand grip strength, arm muscle power, and flexibility with the slam results of wrestling athletes at the Sriwijaya State Sports School. Conducted from September 9 to September 27, 2024, the study involved 15 athletes as participants. Data were collected using test and measurement instruments and analyzed using regression and correlation tests with SPSS version 26. The findings revealed significant relationships between the physical attributes and slam results. First, hand grip strength showed a significant correlation with the slam result, with a significance value of 0.023 (<0.05) and a determination coefficient (R) of 0.988, indicating a perfect correlation. Second, arm muscle power demonstrated a significant relationship with the slam result, with a significance value of 0.00 (<0.05) and an R value of 0.981, also showing a perfect correlation. Third, flexibility had a significant impact on the slam result, with a significance value of 0.000 (<0.05) and an R value of 0.720, indicating a strong correlation. Finally, a combined analysis of hand grip strength, arm muscle power, and flexibility revealed a significant relationship with the slam results, with a significance value of 0.00 (<0.05) and an R value of 0.973, demonstrating a perfect correlation. In conclusion, the study highlights that hand grip strength, arm muscle power, and flexibility significantly contribute to the slam results of wrestling athletes at the Sriwijaya State Sports School, with hand grip strength and arm muscle power showing the strongest correlations, emphasizing the importance of these physical attributes in enhancing wrestling performance.